RELATIONSHIPS OF FREESTYLE SWIMMING PERFORMANCE WITH DYNAMIC STRENGTH AND SHOULDER ISOKINETIC PARAMETERS - Erkan M.; Akdogan E.; Kale M. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
It is thought that upper body dynamic strength and shoulder isokinetic parameters are related with freestyle swimming performance. The purpose of this study was to investigate relationships of freestyle swimming performance with dynamic strength parameters and shoulder isokinetic parameters. Nine male swimmers of Anadolu University Swimming Team [age (year)= 22.9±2.7, body height (cm)= 170.0±5.25, body weight (kg)= 74.1±7.0, BMI= 22.0±2.62 (kg/m2); body fat percent (%)= 12.4±4.9] voluntary participated to the study. Freestyle swimming performances (25m and 50m) were tested by a touchpad chronometer system for a semi-Olympic swimming pool (25m). One repetition maximal test for bench press, clean, and push press was used as upper body dynamic strength parameters. Shoulder isokinetic parameters at 60, 180, and 300o.s-1 angular velocities were extension peak torque, flexion peak torque, and flexion/extension peak torque rate of shoulders. Relationships of freestyle swimming performance with upper body dynamic strength parameters and shoulder isokinetic parameters were analysed with Pearson Correlation Coefficient. Probability level was ≤0.05. The results of this study showed that there were no statistically correlations of freestyle swimming performance with upper body dynamic strength parameters and shoulder isokinetic parameters at 60, 180, and 300o.s-1 angular velocities. In conclusion, there are more studies about different angular velocities of shoulder isokinetic parameters and maximal strength of upper body parameters.